The added worker effect differentiated by gender and partnership status: Evidence from involuntary job loss - Doreen Triebe (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
This paper examines the added worker effect (AWE), which refers to the increase of labor supply of individuals in response to a sudden financial shock in family income, that is, unemployment of their partner. While previous empirical studies focus on married women's response to those shocks, I explicitly analyze the spillover effects of unemployment on both women and men and I also differentiate according to their partnership status (marriage vs. cohabitation). My aim is to evaluate whether intra-household adaptation mechanisms differ by gender and by partnership status. The underlying method is a difference-in-differences setting in combination with an entropy balancing matching procedure. The paper considers plant closures and employer terminations as exogenous forms of unemployment. Using longitudinal data from the German Socio-Economic Panel (SOEP) study from 1991 through 2013, the empirical investigation finds evidence of the existence of an AWE. The effect is largest when a woman enters unemployment and is mainly driven by changes on the intensive margin (increase of hours).
Keywords: D13; J12; J22; 330; added worker effect; plant closure; unemployment; entropy balancing; intra-household adaptation